A phase II study of belinostat (PXD101) in relapsed and refractory aggressive B-cell lymphomas: SWOG S0520. Issue 10 (2nd October 2016) - Puvvada, Soham D.; Li, Hongli; Rimsza, Lisa M.; Bernstein, Steven H.; Fisher, Richard I.; LeBlanc, Michael; Schmelz, Monika; Glinsmann-Gibson, Betty; Miller, Thomas P.; Maddox, Anne-Marie; Friedberg, Jonathan W.; Smith, Sonali M.; et al.
Abstract: Recent advances in diffuse large B-cell lymphomas (DLBCL) have underscored the importance of tumor microenvironment in escaping host anti-tumor responses. One mechanism is loss of major histocompatibility Class II antigens (MHCII) associated with decreased tumor infiltrating T lymphocytes (TIL) and poor survival. Transcription of MHCII is controlled by CIITA which in turn is regulated by histone acetylation. In this study, we hypothesized that HDAC inhibition with belinostat increases MHCII, CIITA expression, TIL and improves patient outcomes. Primary objective was evaluation of toxicity and response. Twenty-two patients were enrolled for the study. Belinostat was well tolerated with mild toxicity. Two partial responses were observed at 5, 13 months after registration for an overall response rate (ORR) (95% CI) of 10.5% (1.3–33.1%), and three patients had stable disease for 4.7, 42.3+, and 68.4 + months with minimum 3-year follow-up. Included correlative studies support the hypothesis and serve as the basis for SWOG S0806 combining vorinostat with R-CHOP.